IMPROVEMENT OF THE CONTROL SYSTEM OF A HYBRID PHOTOVOLTAIC SYSTEM FOR SELF-CONSUMPTION OF A RESIDENTIAL BUILDING WITH CONSUMPTION REGULATION - ШАВЬОЛКІН, О. О.; ПІДГАЙНИЙ, М. О. (Technologies and Engineering, 2024)
Purpose. Improving the management of a hybrid photovoltaic system of a residential building with air conditioning and an adjustable electric boiler for heating water by increasing the degree of use of photovoltaic battery energy for consumption, developing the principles of implementing an energy management system using forecasting. Methodology. Analysis of using possibilities an air conditioner at different air temperatures and photovoltaic battery generation using statistical data. Analysis of boiler temperature conditions, taking into account the energy consumption of the air conditioner and the nature of its power changes over time. Using computer modeling to evaluate results. Results. The structure of the boiler power regulation block with consumption equalization in time and the algorithm for controlling the boiler temperature mode based on the photovoltaic battery generation forecast and the air temperature has been developed Originality. A method for implementing boiler power regulation with leveling the graph of total power consumption over time has been developed. The principle of implementing an energy management system using air temperature forecast and photovoltaic battery generation to set boiler temperature conditions has been developed. This will help to increase the utilization of PV energy and reduce the consumption of electricity from the grid. Practical value. The obtained solutions are the basis for the design of photovoltaic systems for self-consumption of private houses in the case of using an electric boiler in the providing warm water system and air conditioning.